Konjungsi Subordinatif Waktu Dalam Bahasa Minangkabau - Yades, Efri (Puitika, 2024)
This article examines the subordinating conjunctions of time in the Minangkabau language. The conjunctions that will be discussed are the types of time subordinating conjunctions and their meanings. Data was taken using the observation method. The collected data was analyzed using the add and match method. Based on the results of data analysis, there are types of time subordinating conjunctions used, namely as follows: initial time limit, time similarity, time sequence, and end time limit. The time meaning relationships found are: the initial time meaning relationship, the time similarity meaning relationship, the time sequence meaning relationship, and the final time limit meaning relationship.